Understanding the Archaeological Heritage of the Early Mediaeval Cemetery at the Bagruša Site near Petoševci (Archaeologia Adriatica, 2010)
In his contribution, the author strives to evaluate in detail the significance of the archaeological heritage of the early mediaeval cemetery at the Bagruša site near the village of Petoševci near Banja Luka in the Bosnian part of Posavina. Our understanding of this site offers new chronological determinants for both the analysed clan cemetery in rows and also establishing the start of the formation and manifestation of the Bijelo Brdo culture on the southern margins of the central Danube region. In this paper, an interweaving of several cultural circles can be identified.
Keywords: Bagruša near Petoševci; early Middle Ages; Bijelo Brdo culture; Croatian Principality; Greater Moravia; Old Hungarian cultural circle; Byzantine cultural circle; grave goods